Cell-to-Cell Communications in Alcohol-Associated Liver Disease - Osna, Natalia A.; Eguchi, Akiko; Feldstein, Ariel E.; Tsukamoto, Hidekazu; Dagur, Raghubendra S.; Ganesan, Murali; New-Aaron, Moses; Arumugam, Madan Kumar; Chava, Srinivas; Ribeiro, Marcelle; Szabo, Gyongyi; Mueller, Sebastian; et al. (Frontiers in Physiology, 2022)
This review covers some important new aspects of the alcohol-induced communications between liver parenchymal and non-parenchymal cells leading to liver injury development. The information exchange between various cell types may promote end-stage liver disease progression and involves multiple mechanisms, such as direct cell-to-cell interactions, extracellular vesicles (EVs) or chemokines, cytokines and growth factors contained in extracellular fluids/cell culture supernatants. Here, we highlighted the role of EVs derived from alcohol-exposed hepatocytes in activation of non-parenchymal cells, liver macrophages and hepatic stellate cells (HSC). The review also concentrates on EV-mediated crosstalk between liver parenchymal and non-parenchymal cells in the settings of HIV- and alcohol co-exposure. In addition, we presented in vivo and in vitro results on the crosstalk between cell death pathways and inflammasome activation in alcohol-activated hepatocytes and macrophages. Furthermore, we covered highly clinically relevant studies on the role of non-inflammatory factors, sinusoidal pressure and hepatic arterialization in HSC stimulation and subsequent alcohol-induced hepatic fibrogenesis. We strongly believe that the review will disclose major mechanisms of cell-to-cell communications pertained to alcohol-induced liver injury progression and will identify therapeutically important targets, which can be used for alcohol-associated liver disease prevention.